Effect of LiCF3SO3 on L-Chitosan/PMMA Blend Polymer Electrolytes - Khiar, ASA; Radzi, SM; Razak, NA (Taylor & Francis Ltd, 2024)
This paper focuses on the effect of lithium triflate (LiCF3SO3) on the structural and conduction properties of lauroyl (L)-chitosan/poly(metylmethacryalate) (PMMA)-based polymer electrolytes. Films of L-chitosan/PMMA blends and its complexes were prepared using a solution-casting technique. The ionic conductivity of the system was measured over a wide range of frequency between 50Hz-1MHz. Impedance plot for the samples demonstrates two well-defined regions. The disappearance of the high frequency semicircular region led to a conclusion that the current carriers are ions. Sample with 30 wt% of LiCF3SO3 showed the highest conductivity of 7.59 +/- 3.64 x 10(-4) Scm(-1) at room temperature. This is consistent with the results obtained from infrared spectroscopy.